2010
DOI: 10.1002/cjoc.201090380
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐controlled Synthesis of Nanostructure Ramsdellite‐type Manganese Oxide at Atmospheric Pressure

Abstract: Ramsdellite (R-MnO 2 ) was prepared by oxidizing bivalent manganese salts, such as MnCl 2 , MnSO 4 and Mn(NO 3 ) 2 , with NaClO solution using a refluxing process at atmospheric pressure. The products were characterized by X-ray diffraction, fourier transform infrared spectroscopy, transmission electron microscopy, scanning electron microscopy and flame photometry. R-MnO 2 microstructure and morphology were controlled by adjusting reaction temperature, the amount of hydrochloric acid (HCl) and anions of bivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Syntheses of 4-( p -bromophenyl)-6-phenyl-2,2′-bipyridine, 4-phenyl-6-phenyl-2,2′-bipyridine (ph-C^N^N), [(ph-C^N^N)­Pt­(CC–C 6 H 5 )], a 4′-phenyl-2,2′:6′,2″-terpyridine (ph-TPY), [Zn­(ph-TPY) 2 ]­(PF 6 ) 2 , N′-( tert -butoxycarbonyl)- N ′-(phenyl)- p -phenylenediamine, and N , N ′-dibutyl- N , N ′-diphenyl- p -phenylene-diamine have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Syntheses of 4-( p -bromophenyl)-6-phenyl-2,2′-bipyridine, 4-phenyl-6-phenyl-2,2′-bipyridine (ph-C^N^N), [(ph-C^N^N)­Pt­(CC–C 6 H 5 )], a 4′-phenyl-2,2′:6′,2″-terpyridine (ph-TPY), [Zn­(ph-TPY) 2 ]­(PF 6 ) 2 , N′-( tert -butoxycarbonyl)- N ′-(phenyl)- p -phenylenediamine, and N , N ′-dibutyl- N , N ′-diphenyl- p -phenylene-diamine have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…The description of some of the polymorphs of manganese oxide nanomaterials from literature has been given in Tab. 1 [17,[39][40][41][42][43][44][45][46][47]. For a more thorough study of crystal structures, one can go through Ref.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…The addition of AlCl 3 consumed OH À to form AlO 2 À , and also affected the oxidation capacity of NaClO in strong alkaline solution systems. 22,23 The preparation of doped o-LiMnO 2 by one-step hydrothermal synthesis was seldom reported, which was likely due to the precipitation reaction of metal cations and hydroxide ions. In this work, soluble AlO 2 À was formed using AlCl 3 in LiOH solution of high concentration.…”
Section: The Inuence On O-limno 2 Formation Processmentioning
confidence: 99%
“…Under reuxing conditions, sodium hypochlorite (NaClO) could oxidize Mn(II) source to form uniform ramsdellite-type manganese oxide with various morphologies. 22 MnPO 4 $H 2 O and hureaulite containing low-valent Mn(III/II) can also be fabricated by adjusting reactant ratios and reaction temperatures. 22,23 Our previous studies have suggested that manganese minerals with different oxidation states of manganese could be formed when NaClO worked as oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation